2008
DOI: 10.1007/bf03321591
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Occlusal Topography: A Twin Study

Abstract: Aim-This was to determine the relative contribution of genetic factors on the morphology of occlusal surfaces of mandibular primary first molars by employing the twin study model. Methods-The occlusal morphology of mandibular primary first molar teeth from dental casts of 9 monozygotic (MZ) twin pairs and 12 dizygotic (DZ) twin pairs 4 to 7 years old, were digitized by contact-type three-dimensional (3D) scanner. To compare the similarity of occlusal morphology between twin sets, each twin pair of occlusal sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…In other words, a finding of homolateral premolars with high degrees of similarity had a higher chance belonging to identical twins. Their findings of occlusal topology having less variability in identical twins versus fraternal twins has been confirmed in two three-dimensional geometric morphometric studies [67,68]. Townsend et al speculate that since less asymmetry (both directional and fluctuating) was reported in identical and fraternal twins compared with singletons according to findings made by Boklage, "there may be something special about the twinning process [69,70].…”
Section: Asmentioning
confidence: 96%
“…In other words, a finding of homolateral premolars with high degrees of similarity had a higher chance belonging to identical twins. Their findings of occlusal topology having less variability in identical twins versus fraternal twins has been confirmed in two three-dimensional geometric morphometric studies [67,68]. Townsend et al speculate that since less asymmetry (both directional and fluctuating) was reported in identical and fraternal twins compared with singletons according to findings made by Boklage, "there may be something special about the twinning process [69,70].…”
Section: Asmentioning
confidence: 96%
“…Heredity estimations revealed that genetic factors strongly influence occlusal morphology of mandibular primary first molars. 16 According to Consolaro, epigenetics may explain why teeth of the same patient are not exactly the same on both sides. The genetic information that DNA carries is to develop teeth bilaterally equal.…”
Section: Discussionmentioning
confidence: 99%
“…Still, heritability estimates for primary tooth size have confirmed a similarly strong (if not stronger) genetic signature, accounting for well over 50% of observed variation (Di Salvo et al, 1972; Hughes et al, 2000; Mizoguchi, 1998; Townsend, 1980). Outside of metric traits, few heritability estimates have been generated for deciduous teeth, with the exception of crown topography (Su et al, 2008) and orthodontic variables (Chen, 2006; El‐Nofely et al, 1989; Foster & Hamilton, 1969; Harris & Johnson, 1991; Hughes et al, 2001). Deciduous morphology has recently received attention.…”
Section: Quantitative Genetic Studiesmentioning
confidence: 99%